The Effect of Gamma Ray (γ) Irradiation on Optical Absorption of Polymer Film Blend - Ni Nyoman Sri Putu Verawati (Universitas Pendidikan Mandalika, 2020)
Polymer films have become a material for research recently because polymer films have an important role in the application of basic sciences. The polymer film has good mechanical, electrical and optical properties to be used in many applications, one of which is a polymer film that has the potential to be irradiated into a dosimeter. Therefore, modification of polymer film one of which is gamma ray irradiation is important to be further explored. This study aims to explore the effect of gamma ray irradiation on the optical absorption of polymer film blend PVA (polyvinyl alcohol) -trichloroacetid acid (TCA) -methylene blue (MB). Preparation of polymer films by chemical processes using the solvent-casting method. Each polymer film was irradiated with gamma rays with radiation doses ranging from 0 kGy to 14 kGy. Optical absorption was measured using a UV-VIS spectrophotometer with a range of wavelengths ranging from 200 nm to 700 nm. The results showed that three optical absorption peaks were formed on the polymer film PVA-TCA-MB due to gamma ray radiation at wavelengths of 360 nm, 440 nm, and 560 nm. Gamma ray radiation has an effect on optical absorption, where the optical absorption value of polymer film for the first peak (360 nm) and second peak (440 nm) decreased along with the increase in the dose of gamma ray irradiation, but for the third peak (560 nm) there was an increase in the optical absorption value along with an increase in the dose of gamma ray irradiation. The results of further studies are described in this article.